Effects of a Multicomponent Physical Exercise Program on the Physiological Functions of People With Parkinson’s Disease - Gomez-Lopez, Sara (2023)
Introduction: Parkinson's disease (PD) is a progressive neurological disorder characterized by motor and non-motor symptoms that influence the impairment of quality of life. Objective: This research aims to analyze the effects of a multicomponent intervention program based on physical exercise and sport on the physiological functions of people with PD, both with high and low impairment. Methodology: For this purpose, sixteen people (13 men and 3 women) with PD participated in this study, divided into two groups according to their level of impairment, low (GBA, n = 12) and high (GAA, n = 4). A multicomponent physical exercise program intervention was administered to all participants for 4 weeks (2 sessions of 50 minutes per week). A battery of functional tests [Six minutes walk test (6MWT); Single-leg Stance test (SLS); Time Up and Go (TUG) and The five times sit-to-stand Chair (FTSTS)] was performed one week before (T1) and one week after the intervention (T2). Results: The total sample improved significantly on the SLS test (P < 0.05; d > 0.56, moderate). However, analyzing each group according to their level of impairment, the GBA group obtained significant improvements in SLS and 5STS (d= 0.44 - 0.68, P < 0.05), while no significant differences were observed in the GAA group in any of the variables analyzed. Conclusion: The results of the present study show the need for further studies with longer duration and more frequent weekly programs.